Electric field and magnetometer observations of the equatorial electrojet: An IEEY program - Woodman Pollitt, Ronald Francisco (1994)
As part of the IEEY program, a chain of magnetometers was deployed along the Peruvian sector crossing the equatorial electrojet. Simultaneous vertical drift measurements were made using Jicamarca's normal I.S. F-region vertical drift mode as well as oblique coherent E-W electrojet drift measurements. The electrojet component of the magnetogram records can be extracted by subtracting the signature from the non-equatorial stations. As expected there is high correlation between this component and the drifts measured by both radar experiments. One of the days was magnetically disturbed. The distribution and density of the chain of magnetometers should allow us to determine the latitude extend of the fluctuating currents responding to the fluctuating electric field.